2016
DOI: 10.1021/acs.nanolett.6b02696
|View full text |Cite
|
Sign up to set email alerts
|

Single Gold Nanorod Charge Modulation in an Ion Gel Device

Abstract: A reliable and reproducible method to rapidly charge single gold nanocrystals in a solid-state device is reported. Gold nanorods (Au NRs) were integrated into an ion gel capacitor, enabling them to be charged in a transparent and highly capacitive device, ideal for optical transmission. Changes in the electron concentration of a single Au NR were observed with dark-field imaging spectroscopy via localized surface plasmon resonance (LSPR) shifts in the scattering spectrum. A time-resolved, laser-illuminated, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 30 publications
(59 reference statements)
6
69
0
Order By: Relevance
“…Based on the understanding of electron injection on the PRRS spectrum of a single AgNP, the effect of electrochemical reduction on the PRRS spectrum of an oxidized single AgNP was studied . In this case, freshly immobilized AgNPs were repeatedly oxidized at +0.4 V and reduced at −0.4 V. As shown in Figure B, when a potential of +0.4 V was applied, the PRRS peak showed an obvious redshift and a decrease in intensity, as reported above.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the understanding of electron injection on the PRRS spectrum of a single AgNP, the effect of electrochemical reduction on the PRRS spectrum of an oxidized single AgNP was studied . In this case, freshly immobilized AgNPs were repeatedly oxidized at +0.4 V and reduced at −0.4 V. As shown in Figure B, when a potential of +0.4 V was applied, the PRRS peak showed an obvious redshift and a decrease in intensity, as reported above.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical studies tracking Raman spectroscopy within gold gaps that sandwich a single molecular layer have proposed that the potential-dependent Raman emission depends on molecular torsion angles 9 . Shifts in the scattering resonance of single Au nanoparticles following application of a negative bias have been attributed to an increase in the NP electron concentration ( ) via electron transfer from the ITO substrate 11,12 . However this work suggests that the scattering cross-section scat ( ) is surprisingly nonlinear.…”
mentioning
confidence: 99%
“…Chemical charging or discharging is therefore an effective tool to tune surface plasmon resonance frequencies in plasmonic nanoparticles, through alteration of the electron density. As a general observation, an increase in free electron density results in a blue‐shift of the LSPR band, while removal of charges leads to a shift toward longer wavelengths . LSPR shifts due to changes in the electron density of silver and gold nanoparticles have been previously described .…”
Section: Introductionmentioning
confidence: 72%
“…LSPR shifts due to changes in the electron density of silver and gold nanoparticles have been previously described . In these reports, nanoparticles either in colloidal solution or immobilized on solid surfaces were charged through the addition of a strong reducing agent or by applying an electrochemical potential . Mulvaney and co‐workers have experimentally demonstrated that Au nanorods exhibit a drastic extinction blue‐shift when their free electron density is increased, through oxidation of added borohydride ions .…”
Section: Introductionmentioning
confidence: 99%